2005
DOI: 10.1007/s11176-005-0211-4
|View full text |Cite
|
Sign up to set email alerts
|

Energy of Formation of an Acyclic N-Methyltrifluoromethanesulfonamide Dimer

Abstract: The energy of formation of an open-chain N-methyltrifluoromethanesulfonamide dimer stabilized by the N3H...O=S hydrogen bond is 20.1 kJ mol !1 (CH 2 Cl 2 ). This value exceeds by~12 kJ mol !1 the energy of formation of cyclic secondary methanesulfonamide self-associates per hydrogen bond.A specific property of trifluoromethanesulfonamide and its N-methyl derivative is their ability to form cyclic dimers in nonpolar inert solvents and in the gaseous phase [1,2]. According to the data of IR and Raman spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…As shown previously, this calculation procedure quite satisfactorily reproduces the energy of formation of cyclic homoassociates of trifluoroacetic acid and N-methylacetamide [7] and geometric parameters of the trifluoromethanesulfonic acid molecule, as well as of some other compounds with intra-and intermolecular hydrogen bonds [8,9].…”
supporting
confidence: 72%
“…As shown previously, this calculation procedure quite satisfactorily reproduces the energy of formation of cyclic homoassociates of trifluoroacetic acid and N-methylacetamide [7] and geometric parameters of the trifluoromethanesulfonic acid molecule, as well as of some other compounds with intra-and intermolecular hydrogen bonds [8,9].…”
supporting
confidence: 72%
“…This is indicative of the formation of stronger hydrogen bonds typical of cyclic associates, just those which sulfonamides I and III form in CCl 4 solution, although in the crystal compound I, according to the XRD data, it forms chains by means of Н-bonds of 2.117 Å length [35], apparently, due to the packing effects. The comparison of the experimental and theoretical spectral shifts of N-trimethylsilyltriflamide II suggests that in CCl 4 solution it forms linear associates, unlike the earlier studied Nmethyltriflamide, which in CCl 4 solution forms two types of self-associates, both linear and cyclic [41]. EXPERIMENTAL IR spectra of solutions were recorded on a FTIR Varian 3100 spectrophotometer.…”
Section: Moleculementioning
confidence: 99%
“…Self-association of triflamide was studied theoretically and experimentally in the gas phase and in inert media. These studies have shown that because of a high NH-acidity of triflamide, the equilibrium between the monomeric molecules and various H-bonded self-associates (linear and cyclic dimers, trimers and tetramers) exists even in vapors up to 435 K. [3] Supramolecular structure of triflamide as a function of basicity and polarity/polarizability of the solvent was studied, [4] as well as transformation of its self-associates into the solvate H-complexes in protophilic media. [5] However, strange as it might seem, no direct determination of the structure of triflamide has been reported.…”
Section: Introductionmentioning
confidence: 99%